2010
DOI: 10.1038/ijo.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length of subcutaneous adipose tissue cells is shorter in obese and formerly obese subjects

Abstract: Obesity and increased fat mass are associated with increased adipocyte proliferation. Telomere length can serve as a biomarker of a cell's biological (vs chronological) age. To gain insight in the physiology of adipose tissue, we aimed to investigate telomere length in subcutaneous adipose tissue in relation to age and obesity. Telomere length was measured in 72 subcutaneous adipose tissue samples from 21 nonobese and 51 obese subjects. Telomere length of subcutaneous adipose tissue cells was negatively associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 13 publications
4
39
1
Order By: Relevance
“…Literature on the association of adiposity and LTL is based on cross-sectional studies and the findings are conflicting as some of the studies, including ours, found no association between BMI or other measures of adiposity and LTL, 4,5,22,[47][48][49] whereas some have reported significant inverse associations. 7,8,16,19,50 A recent cross-sectional study assessing total body and abdominal obesity in subjects aged 8-80 years noticed that the negative association between BMI and LTL is stronger among young subjects compared with the old. 7 Previous studies noticed LTL to be positively associated with physical activity 17 and socioeconomic status 19 and negatively associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature on the association of adiposity and LTL is based on cross-sectional studies and the findings are conflicting as some of the studies, including ours, found no association between BMI or other measures of adiposity and LTL, 4,5,22,[47][48][49] whereas some have reported significant inverse associations. 7,8,16,19,50 A recent cross-sectional study assessing total body and abdominal obesity in subjects aged 8-80 years noticed that the negative association between BMI and LTL is stronger among young subjects compared with the old. 7 Previous studies noticed LTL to be positively associated with physical activity 17 and socioeconomic status 19 and negatively associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Accelerated telomere shortening is associated with aging and aging-related diseases, such as hypertension, coronary heart disease and heart failure. [5][6][7] Shorter LTL has also been associated with higher body mass index (BMI), 7,8 insulin resistance and type 2 diabetes, 9,10 as well as with some forms of cancer. 11,12 Genetic, epigenetic and environmental factors influence LTL.…”
Section: Introductionmentioning
confidence: 99%
“…Telomere length shortens with every cell division, so telomere attrition is a fundamental aspect of cell proliferation [6]. Moreno-Navarrete et al [7] reported that the telomere length of subcutaneous adipose tissue in obese subjects was significantly shorter than in non-obese subjects and suggested that telomere length is an adipose tissue expansion marker. Recently, Lakowa et al [8] showed that the telomere length of subcutaneous adipose tissue in obese subjects was shorter than in visceral adipose tissue.…”
Section: Introductionmentioning
confidence: 98%
“…Activation of p53 occurs in response to shortened telomeres in ageing cells. Interestingly, shorter telomeres have been described in adipose tissue cells from obese individuals, being even shorter in formerly morbidly obese individuals compared with never morbidly obese individuals of a similar age and degree of obesity [13].…”
Section: New Inroads Into the Association Between The Innate Immune Smentioning
confidence: 99%